Numerical simulation of rock cutting using 2D AUTODYN - Woldemichael, D.E. (Institute of Physics Publishing, 2015)
In a drilling process for oil and gas exploration, understanding of the interaction between the cutting tool and the rock is important for optimization of the drilling process using polycrystalline diamond compact (PDC) cutters. In this study the finite element method in ANSYS AUTODYN-2D is used to simulate the dynamics of cutter rock interaction, rock failure, and fragmentation. A two-dimensional single PDC cutter and rock model were used to simulate the orthogonal cutting process and to investigate the effect of different parameters such as depth of cut, and back rake angle on two types of rocks (sandstone and limestone). In the simulation, the cutting tool was dragged against stationary rock at predetermined linear velocity and the depth of cut (1,2, and 3 mm) and the back rake angles(-10°, 0°, and +10°) were varied. The simulation result shows that the +10o back rake angle results in higher rate of penetration (ROP). Increasing depth of cut leads to higher ROP at the cost of higher cutting force.